Integrating Artificial Intelligence and Digital Marketing to Enhance The Customer Experience of Spotify Users - Firjatullah, Naufal Arya; Suryadi, Nanang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of this quantitative explanatory research is to identify the effects of artificial intelligence and digital marketing on customer experience. Using purposive sampling technique, 120 Spotify users with the minimum age of 17 years, either male or female, who have used artificial intelligence, and have seen the digital marketing of the application via social media were selected as the respondents. The data was harvested from Likert questionnaires and analyzed using multiple linear regression. These findings indicate that there are two variables with positive and significant effects on the customer experience: artificial intelligence and digital marketing. Therefore, Spotify is suggested to regularly make innovations on features that uses artificial intelligence, to enhance its marketing strategies by increasing activities in social media such as Instagram, Twitter, and TikTok to share appealing contents, and to be involved in trends popular among younger audiences. Additionally, it is also suggested that Spotify conduct their marketing campaigns by directly involving its users.